Optimalisasi Sektor Pertanian di Kabupaten Jombang untuk Perkembangan Ekonomi Daerah - Muhammad Sofwan; Handi Widyawan; Effy Indriati (Fakultas Pertanian, Universitas Darul Ulum, 2025)
The agricultural sector in Jombang Regency serves as the backbone of the regional economy, contributing significantly to the Gross Regional Domestic Product (GRDP), accounting for approximately 27.3%, valued at Rp 21.4 trillion (BPS, 2024). Nevertheless, the sector's direct contribution to Local Own-source Revenue (PAD/Pendapatan Asli Daerah) remains relatively low because most agricultural products are marketed as raw commodities with limited value addition. This research aims to analyze the agricultural sector's contribution to GRDP and PAD, identify the existing potential and constraints, and formulate optimal strategies to enhance the sector's role in local economic development. The research employed a mixed-methods approach, utilizing quantitative analysis through the Location Quotient (LQ) to identify base commodities, and qualitative analysis via in-depth interviews with key stakeholders, subsequently analyzed using the SWOT matrix. The findings indicate that the main base commodities in Jombang include rice (padi), sugarcane (tebu), and horticulture, all possessing high comparative advantage. This significant potential is supported by diverse agro-climatic conditions and the availability of productive human resources, especially young farmers. However, several structural constraints still impede optimization, including limited access to capital/financing, uneven irrigation infrastructure, weak farmer institutional capacity, and limited product quality certification. The recommended strategies include: (1) developing downstreaming (hilirisasi) of agricultural products to increase value addition; (2) strengthening farmer institutions through professional cooperatives; (3) implementing modern agricultural innovation and technology; and (4) establishing an integrated agropolitan area that connects with MSMEs, tourism, and export markets. Implementation of these strategies is projected to boost PAD by approximately Rp 80–100 billion annually, create new job opportunities, and strengthen regional fiscal independence. Thus, reinforcing the agricultural sector in Jombang Regency not only implies improving farmer welfare but also serves as a strategic instrument for the local government in building a competitive, inclusive, and sustainable local economy.